Implementasi Promosi Kesehatan melalui Germas (Gerakan Masyarakat) Bebas ISPA di Desa Teluk Kecapi, Kabupaten Ogan Ilir, Sumatera Selatan - Kiani, Safa Tiara; Rohmah, Ulfa Nur; Latifin, Khoirul; Purwanto, Sigit; Fitriani, Dhia Diana (Shihatuna : Jurnal Pengabdian Kesehatan Masyarakat, 2025)
Acute respiratory infection (ARI) is a major source of morbidity and mortality from infectious illnesses worldwide, accounting for approximately four million fatalities each year and having relatively high mortality rates among newborns, children, and the elderly, particularly in low- and middle-income countries. Through one of the health promotion initiatives, this action aims to raise public awareness. Health promotion is carried out through lectures and discussions about the Acute Respiratory Infection-Free Community Movement. The results of the activity have been the implementation of Health examinations and increased public knowledge through observation and evaluation of open questions with the given theme. It is hoped that health promotion on the Acute Respiratory Infection-Free Movement will become a sustainable public health intervention model and be able to provide long-term benefits to the community.